RESPON SISWA TERHADAP PEMBELAJARAN DALAM JARINGAN (DARING) PADA MATA PELAJARAN MATEMATIKA - Denny Andriani; Krisdianto Hadi Prasetyo; Erika Laras Astutiningtyas (Universitas Veteran Bangun Nusantara, 2020)
The objective of this study is to determine students' responses to learning in the network (online) in mathematics. This research uses a descriptive method with a qualitative approach. Data collection technique is questionnaire. The questionnaire consisted of positive and negative statements totaling 20 statements. The questionnaire is distributed via Googleform. Data analysis techniques are data reduction, data presentation and conclusion. The subjects are 29 students of Class XI MIPA 1 of SMA Negeri 1 Weru in the academic year 2019/2020. The result shows that the average percentage of student responses in mathematics received positive criteria. With the average percentage of students' responses to the first indicator, namely interest of 83.62% so it is included in the positive criteria. In the second indicator, motivation is 74.14% so it is included in the positive criteria. The third indicator is satisfaction at 80.17% so it is included in the positive criteria. In the fourth indicator, interest is 73.49% so it is included in the positive criteria. And the fifth indicator is the response of 75.43% so it is included in the positive criteria.